Neurokinin-1 Receptor Antagonists as Anticancer Drugs - Muñoz, Miguel; Coveñas, Rafael (Letters in Drug Design & Discovery, 2019)
Background: Human tumor cells lines and tumor samples overexpress the neurokinin-1 receptor (NK-1R). Substance P (SP), after binding to NK-1Rs, induces tumor cell proliferation, an antiapoptotic effect and promotes angiogenesis and the migration of cancer cells for invasion and metastasis. Methods: In contrast, NK-1R antagonists block the previous pathophysiological actions mediated by SP. These antagonists promote the death of tumor cells by apoptosis. Peptide and non-peptide NK-1R antagonists have been reported. Results: Peptide NK-1R antagonists show chemical modifications of the SP molecule (L-amino acids being replaced by D-amino acids), whereas non-peptide NK-1R antagonists include numerous compounds with different chemical compositions while showing similar stereochemical features (affinity for the NK- 1R). Currently, there are more than 300 NK-1R antagonists. Conclusion: In combination therapy with classic cytostatics, NK-1R antagonists have additive or synergic effects and minimize the side-effects of cytostatics. The effect of NK-1R antagonists as broad-spectrum anticancer drugs is reviewed and the use of these antagonists for the treatment of cancer is suggested.
Keywords: apoptosis